ARE PERIODONTAL TISSUES AND PERIODONTAL HEALTH IMPACTED BY FOOD SUPPLEMENTS (PROTEIN AND AMINOACIDS, NATURAL HERBAL PRODUCTS, MINERALS)? – REVIEW - George Alexandru Maftei; Oana Ciurcanu; Odette Luca; Liliana Pasarin; Cristina Popa; Mihaela Mares; Maria Alexandra Martu; Ionut Luchian (Romanian Journal of Medical and Dental Education, 2022)
The aim of this review is to provide an overview of the current evidence of some popular food supplements and superfoods that might be of interest in periodontology.